2001
DOI: 10.1002/jnr.10111
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of thyroid hormone receptor isoforms in mouse oligodendrocytes

Abstract: Double and triple immunocytochemistry with stage-specific markers and specific antireceptor antibodies was used to study expression of nuclear thyroid hormone receptor (TR) isoforms in cultured mouse oligodendrocytes. To evaluate the coexpression of each TR isoform, antibodies were raised in rabbits and mice against specific regions of alpha1-TR and alpha2-TR common to both alpha isoforms and beta1-TR. Their specificities were assessed by Western blotting and by immunocytochemistry on rat hepatocytes. Oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…There appears to be general consensus that both OPCs and OLGs express TRα and that OLGs express TRβ (Carré et al, 1998). According to Bury et al (2002), TRα and TRβ colocalize in OLGs before CNPase is expressed. Thus, it might be speculated that, during the initial stages of OLG differentiation, Tf triggers TRα expression in the SVZ and promotes undifferentiated proliferating cells to become responsive to this trophic factor.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be general consensus that both OPCs and OLGs express TRα and that OLGs express TRβ (Carré et al, 1998). According to Bury et al (2002), TRα and TRβ colocalize in OLGs before CNPase is expressed. Thus, it might be speculated that, during the initial stages of OLG differentiation, Tf triggers TRα expression in the SVZ and promotes undifferentiated proliferating cells to become responsive to this trophic factor.…”
Section: Discussionmentioning
confidence: 99%
“…While some groups (Baas et al, 1994a; Baas et al, 1994b; Billon et al, 2002; Billon et al, 2001; Bury et al, 2002) report expression in differentiated OLs but not OPCs, others have found THRβ1 to be present in both cell types (Barres et al, 1994). These discrepant findings may be explained by changes in the expression of THRβ1 within OPCs that are dependent on the “age” of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…*A statistically significant difference between these values in the figure. Color images available online at www .liebertonline.com/scd progressively decreases as OP cells mature into oligodendrocytes, and it is therefore primarily a marker of OP cells [63]. TRa was detected in the nucleus of ADM cultured in GM, in a punctate staining pattern that colocalized with DAPI (Fig.…”
Section: Adm Express the Tra And Exhibit Increased Tertiary Branchingmentioning
confidence: 98%